2015
DOI: 10.1055/s-0035-1553496
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Contrast-Enhanced Endoscopic Ultrasonography for the Guidance of Fine-Needle Aspiration in Solid Pancreatic Masses

Abstract: The global accuracy of fine-needle aspiration guided by endoscopic ultrasound (EUS-FNA) for pancreatic adenocarcinoma is about 85 %. The use of contrast agents during EUS to highlight vessels and the necrotic parts of pancreatic masses may improve biopsy guidance. Our aim was to assess whether the guidance of FNA by harmonic contrast-enhanced endoscopic ultrasound (CH-EUS) would increase diagnostic accuracy relative to conventional EUS-FNA in the same pancreatic masses. In a prospective study, EUS-FNA was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 33 publications
4
50
0
1
Order By: Relevance
“…Although this does not obviate the need for EUS-FNA it might certainly better select the patients and bring significant improvements in the methodology of EUS-FNA concerning the types of needle used, number of passes, cytology versus microhistology (core) biopsy, dedicated passes for ancillary studies, etc [24]. A recent published study revealed that CEH-EUS guided FNA has a better accuracy [25]. Moreover, fewer needle passes are required to obtain samples [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although this does not obviate the need for EUS-FNA it might certainly better select the patients and bring significant improvements in the methodology of EUS-FNA concerning the types of needle used, number of passes, cytology versus microhistology (core) biopsy, dedicated passes for ancillary studies, etc [24]. A recent published study revealed that CEH-EUS guided FNA has a better accuracy [25]. Moreover, fewer needle passes are required to obtain samples [26].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic neuroendocrine tumors typically show hyperenhancement followed by "wash-out", filling defects being predictive of malignancy [170]. CHI-EUS can be used complementary to EUS-FNA in order to increase the diagnostic yield and accuracy through the guidance of the needle during real-time CEUS [171].…”
Section: Contrast Harmonic Imaging Endoscopic Ultrasoundmentioning
confidence: 99%
“…CE-EUS with low mechanical index has been used similarly to transabdominal CEUS to differentiate between pseudotumoral CP and ductal adenocarcinoma, but also to guide FNA in order to avoid avascular areas, improving the diagnostic accuracy of FNA [54]. Quantitative postprocedural assessment of uptake of the contrast agent has been proven useful to improve the accuracy of CE-EUS with low mechanical index for differentiating between the two entities [55,56].…”
Section: Contrast-enhanced Endoscopic Ultrasound (Ce-eus)mentioning
confidence: 99%